On S.A Strarostin's Altajskaja problema i proisxozdenie japonskogo jazyka (The Altaic Problem and the Origin of the Japanese Language). - Miller, Roy Andrew.
Ural Altaische Jahrbücher,13 (1994) 68-107 ss.